Long non‐coding RNA AGER‐1 functionally upregulates the innate immunity gene AGER and approximates its anti‐tumor effect in lung cancer. Issue 3 (14th November 2017) - Pan, Zihua; Liu, Li; Nie, Wenjing; Miggin, Sinead; Qiu, Fuman; Cao, Yi; chen, Jinbin; Yang, Binyao; Zhou, Yifeng; Lu, Jiachun; Yang, Lei
Abstract : Little is known about long non‐coding RNA (lncRNA) related to innate immunity in lung cancer. The advanced glycosylation end‐product specific receptor (AGER) belongs to the immunoglobulin superfamily, and currently, is the only innate immune pattern‐recognition receptor whose abnormal expression has been detected in lung cancer. We aimed to explore the lncRNA that is related to AGER and test its effect on lung carcinogenesis. We selected one lncRNA whose chromosome location is in close proximity to AGER namely lnc‐AGER‐1 (defined as lncAGER). The expression of lncAGER was tested in 276 pairs of lung cancer tissues and adjacent lung normal tissues, and its correlation with lung cancer clinical progress was analyzed. A series of assays were further used to assess the biological function of lncAGER on lung cancer development, tumor immunity and autophagy. LncAGER expression was moderately correlated with AGER expression ( r = 0.360, P = 2.15 × 10 −18 ) underlying a mechanism that lncAGER upregulates AGER by competitively binding to miRNA‐185. LncAGER was significantly down‐regulated in 76.4% of lung cancer tissues compared to adjacent normal tissues due to promoter hypermethylation. Over‐expression of the lncRNA resulted in significant decreases in proliferation rate, migration ability, colony formation efficiency of lung cancer cells and tumor growth in nude mice. Notably, lncAGER possibly conduced to enhancement of cytotoxic effect of THP1. Additionally, the lncRNA also promoted cell apoptosis by strengthening autophagy. Taken together, these observations suggest that lncAGER has an inhibitory effect on lung cancer development via AGER, which may serve as a target for lung cancer treatment.